A experiência do cuidar: o (des) amparo do cuidador familiar - Carvalho, Maria Cristina Guapindaia (2010)
This study aims to characterize the family caregivers of dependent elder people, and to identify the presence of stress, strain and / or minor psychiatric symptoms in these individuals. Additionally, the study examines the relationship between stress and mental distress with social-demographic factors related to the caring activity. This is a cross-sectional and prospective study conducted from July to December 2009, which evaluated 69 caregivers of dependent elder people treated at the Clinic of Geriatrics, Hospital do Servidor Publico Municipal (Municipal Hospital of Civil Servants). By means of structured interview, we applied a questionnaire to characterize the caregivers and the patients, the Zarit stress scale, the SRQ-20 mental distress scale and the Hamilton-21 Depression Scale. The results showed that the investigated caregivers, during the research, were in average 58.72 years old, with 89.86% of them being women, 52.17% being daughters and 36.23% being wives. They were taking care of the patient for 4 years and six months, in average. It was found that 85% of them haven t any social support and 75.36% of them did not receive any help whatsoever from other family members. Regarding to the level of stress, 44.93% of the caregivers presented a moderated level and 34.78% presented levels varying from moderate to severe. Regarding the presence of minor psychiatric symptoms, 68.12% presented mental disorders and all of them were classified as bearers of mild depression, in the Hamilton-21 scale. Regarding to the use of drugs, 34.78% reported the use of antidepressants and 7.25% reported the use of anxiolytics. Regarding to the variables associated to stress, it was found that the dependence of the patient, his/her persistent behavior and the use of antidepressants by the caregiver increased the estimation of stress. It also was found that when the prior relationship between caregiver and the dependent elder person was considered as good, the stress levels were lower, and if the previous relationship was considered poor, the stress increased. With respect to mental suffering, when the dependency factor was perceived as a major disturbance, the chances of presentation of minor psychiatric symptoms by the caregiver were nine times higher. The data show the great demand in the caring activities, the overhead inherent to this task and the stress that it can cause, with consequences for the mental health of the caregiver and the quality of care provided